Análisis de la textura de las microcápsulas en función de la formulación (2017)
The objective of this study was to analyze the effect of the formulation on the texture of the capsules when performing an interfacial polymerization, varying amounts of amine type and polymeric MDI. This, to obtain results that contribute to the development of microcapsules for the implementation in the agrochemical industry. For this, 0.5, 1.0 and 1.5 g of polymeric isocyanate (PAPI 27) and 0.5, 1.0 and 1.5 mL of diethylenetriamine (DETA) and triethylenetetramine (TETA) at 12% were used. The encapsulated active ingredient was xylene. A texture analysis (TPA) was performed by means of the standardization of a procedure that allowed the measurement of the sample using the TA texturometer, HD plus Texture Analyzer (Stable Micro Systems) every 10 minutes for 2 hours. In addition, a 3-factor factorial experiment was designed to study the effect of the amine type (DETA, TETA), formulation (0.5, 1.0, 1.5), reaction time and interaction between them on hardness and Firmness of the microcapsules...